Pengaruh Pergantian Auditor, Opini Audit, Ukuran Perusahaan, Dan Laba Rugi Terhadap Audit Report Lag (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2011-2015) - Apitaningrum, Aprilia, Dr. Erma Setiawati, MM, CA (2017)
The aim of this research was to test and analyze the effect of turn of the Auditor, the Audit Opinion, the size of the company, and the Profit Loss on manufacturing company listed in the 2011-2015 period BEI. The number of the sample in this research is 332 manufacturing company. Analysis of the multiple linear regression using data to test and prove the hypothesis of the study. The results showed the turnover of Auditors and Audit Opinion of the Audit Report to not Lag as evidenced by the level of significance of the variables more than 0.05. While the size of the company and the Income effect significantly to Audit Report Lag because of the significance of the variable levels of less than 0.05. Keywords : Turn Of The Auditor, The Audit Opinion, The Size Of The Company, Profit Loss, and Audit Report Lag.